THE SETTLEMENT MODEL AGAINST CREDIT AGREEMENTS BETWEEN CREDITORS AND DEBTORS - Anis Mashdurohatun; Eyrsa Setya Kurnia (UNISSULA, 2020)
The purpose of this study is to analyze the factors that cause bad credit to credit agreements between creditors and debtors and to formulate a model of bad credit settlement against credit agreements between creditors and debtors. This study uses an empirical juridical approach. This study found that the factors causing the occurrence of bad credit are due to internal factors of the bank (creditors), namely ignoring bank prudential principles, especially the 5C principle, where banks are less careful in assessing potential debtors, and external factors (debtors), where the debtor's business decreases, debtors are not clever in managing their business, debtors have large debts, credit is not used properly, hidden credit and fictitious credit. The non-performing loan settlement model puts forward the principles of taawun and tawazun, with several stages, namely subpoena, credit restructuring and, / or credit settlement by selling collateral as a last resort.